Improvement and Efforts to Maintain Health Immunity in Pediatric Patients at Dr. H. Abdul Moeloek Hospital, Lampung Province - Komarudin, Mamay; Sutisna, Sutisna; Kusuma, Jaka Wijaya; Hamidah, Hamidah (Yayasan Education and Social Center, 2024)
The purpose of this service program is to increase and maintain children's health immunity in Lampung Province through a holistic approach that involves education, collaboration, and community participation. The implementation of the program includes the identification of health needs through surveys, counseling, practical workshops, and community activities involving parents and children. The results obtained showed a significant increase in parents' knowledge and awareness of the importance of balanced nutrition and a healthy lifestyle, as well as improvements in children's health status. The program also succeeded in creating dynamic interaction between participants and medical personnel, as well as facilitating the development of a culture of health among children. The challenges faced during implementation, including the diversity of public understandings related to nutrition, provide important insights for future communication strategy adjustments. The use of technology and digital platforms is expected to expand the reach of the program and increase interaction with the community. With a commitment to conduct ongoing research and collaborate with various stakeholders, the program aims to provide data-driven and relevant health policy recommendations for decision-making in the region. Overall, this service program emphasizes the importance of collaboration and innovation in creating an environment that supports children's health. With continuous efforts, it is hoped that a healthy and competitive next generation can be realized, as well as improve the quality of life of the community as a whole. Investment in child health is a strategic priority that is expected to have a positive impact on the future of the nation